TRAUMATIC EXPERIENCES IN UNDER THE TAMARIND TREE BY NIGAR ALAM - Nuristama, Ramadhina Ulfa (Universitas Negeri Surabaya, 2024)
This study aims to explain the traumatic experiences of the main character, Rozeena, in Under the Tamarind Tree by Nigar Alam. By using a psychological overview of the Under the Tamarind Tree Novel. This article conveys the psychological condition of the main character in the Under the Tamarind Tree novel by Nigar Alam using a descriptive qualitative approach. The research results showed trauma experienced by the main character in the book, which conveys traumatic events since the main character's childhood that affect the main character's life in adulthood. From the existing data, it can be concluded that there are reasons why the main character got traumatized from the main character's childhood until how the main character overcame her trauma in the later days.